2016
DOI: 10.1590/0366-69132016623632005
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of porous gehlenite and anorthite based ceramics using low price raw materials

Abstract: Porous ceramics of good quality cost a lot in the world market, which has limited their use in developing countries. This is why this work was mainly devoted to prepare low-cost and good quality ceramics, using kaolin (DD2 type) and calcite (CaCO3) available in abundance in Algeria. Based on previous results, 28 wt% CaCO3 ceramic was selected. The presence of CaCO3 favors to achieve porous samples characterized by a high percentage of porosity due to the CO2 release and CaO formation during its calcination at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…The clay consisted mainly of aluminum silicate (Al 2 SiO 5 ), intended for the manufacture of the tubular microporous support. The method of tubular support preparation can be summarized in the following steps [28,29]:…”
Section: The Methods Of the Membrane Support And Ceramic Membrane Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The clay consisted mainly of aluminum silicate (Al 2 SiO 5 ), intended for the manufacture of the tubular microporous support. The method of tubular support preparation can be summarized in the following steps [28,29]:…”
Section: The Methods Of the Membrane Support And Ceramic Membrane Preparationmentioning
confidence: 99%
“…Figure 6 represents XRD reflections of the support at a temperature of 1100 • C for 1 h. The main phase identified in the membrane support was the anorthite (CaO, Al 2 O 3 , 2SiO 2 ) which was a predominant phase. This phase was very important because of its promising physical and mechanical properties [5,29].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…[5,44]. The particle size distribution of this material was determined by the dynamic laser beam scattering (DLBS) technique; this method gave an average particle size of 2.2 μm [45]. The kaolin powder was obtained by calcination of the final ground mineral at 520 °C for 1 h. The CaCO 3 powder was calcined at 900 °C for 12 h then hydrated in bi-distilled water and followed by a second calcination at 800 °C for 2 h. The quantitative analysis of these calcium carbonates showed that the purity of this raw material is about 99.7%, using X-ray fluorescence (XRF) analysis.…”
Section: Cerâmicas De Boa Qualidade Têm Alto Custo O Que Limita O Sementioning
confidence: 99%
“…As reported in [46], this raw material may be classified as a high-purity calcium oxide (CaO ≥99.0%). The particle size distribution of calcite was determined by DLBS, which gave an average particle size of 4.8 μm [45].…”
Section: Cerâmicas De Boa Qualidade Têm Alto Custo O Que Limita O Sementioning
confidence: 99%
“…Between 200 and 450°C, there was a mass loss of 2.8 (F20), 3.0 (F30), and 3.5% (F40) associated with the decomposition of organic matter. Between 650°C and 750°C, CaCO 3 (calcite) decomposes, releasing CO 2 and forming CaO 22,23 …”
Section: Resultsmentioning
confidence: 99%